2013
DOI: 10.1038/srep02157
|View full text |Cite
|
Sign up to set email alerts
|

Continuous DOPA synthesis from a single AAV: dosing and efficacy in models of Parkinson's disease

Abstract: We used a single adeno-associated viral (AAV) vector co-expressing tyrosine hydroxylase (TH) and GTP cyclohydrolase 1 (GCH1) to investigate the relationship between vector dose, and the magnitude and rate of recovery in hemi-parkinsonian rats. Intrastriatal injections of >1E10 genomic copies (gc) of TH-GCH1 vector resulted in complete recovery in drug-naïve behavior tests. Lower vector dose gave partial to no functional improvement. Stereological quantification revealed no striatal NeuN+ cell loss in any of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…Numerous studies using direct administration of AAV vectors with different serotypes in small animal models have demonstrated robust transduction rates 71-74 . Additionally, gene therapy using viral vectors has been successfully translated to clinical practice, however, its use has uncovered multiple issues that need to be addressed before viral delivery of optogenetics can be used clinically in humans.…”
Section: Limitations Of Optogenetic Applicationsmentioning
confidence: 99%
“…Numerous studies using direct administration of AAV vectors with different serotypes in small animal models have demonstrated robust transduction rates 71-74 . Additionally, gene therapy using viral vectors has been successfully translated to clinical practice, however, its use has uncovered multiple issues that need to be addressed before viral delivery of optogenetics can be used clinically in humans.…”
Section: Limitations Of Optogenetic Applicationsmentioning
confidence: 99%
“…Analogous to the triple therapy approach currently used in clinical trials utilizing a lentivirus vector, the development of an AAV vector capable of delivering TH and GCH is also being pursued. Recently, co-expression of TH and GCH genes on a single AAV vector has been achieved and has been tested in hemiparkinsonian rats and nonhuman primates [51]. A dose-dependent functional recovery associated with enhanced levodopa production was observed following treatment in unilateral 6-OHDA-lesioned rats.…”
Section: Aav-th-gchmentioning
confidence: 99%
“…Further investigation revealed that this cell loss was most likely associated with levodopa production and its downstream effects on pallidal cells. Moreover, it was determined that the dose of the TH-GCH1 vector can be adjusted to retain efficacy without causing significant toxicity to globus pallidus or striatal neurons [51]. However, when tested in primates, treatment with AAV-TH-GCH did not result in any beneficial effect or functional improvement during a 6-month assessment period.…”
Section: Aav-th-gchmentioning
confidence: 99%
“…A recent single-cell RNA-seq analysis revealed that dopamine neurons derived from both mouse and human PSCs represent many, although not all, subtypes found in the fetal ventral midbrain of the two species 5 , suggesting that further work may be needed to refine differentiation protocols. Previous gene therapy trials for neurodegenerative disease have used viral vectors to genetically alter striatal cells to secrete neuroactive molecules in animal models of parkinsonism 9,10 . The two main strategies have been to introduce either enzymes (e.g.…”
mentioning
confidence: 99%
“…TH, AADC, GTP-cyclohydrolase) that will enable nondopaminergic cells to synthesize dopamine 8 or trophic factors (e.g. CNTF, GDNF) that may exert neuroprotective influence on ongoing dopaminergic degeneration 9 . However, such in vivo gene therapies do not fundamentally alter the underlying primary phenotypes of the transfected host cells, synthesis and release of the transfected molecules is essentially unregulated, and initial clinical results have not been compelling 11 .…”
mentioning
confidence: 99%